Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/srep44015
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms and Pharmacogenomics for the Clinical Efficacy of Methotrexate in Patients with Rheumatoid Arthritis: A Systematic Review and Meta-analysis

Abstract: Methotrexate (MTX) is widely used and considered a first-line disease modifying anti-rheumatic drug (DMARD) for the treatment of rheumatoid arthritis (RA). Many of the relevant genes have been investigated to estimate the association between gene polymorphisms and MTX effectiveness in RA patients, although inconsistent results have been reported. A systematic review and meta-analysis were performed to identify genetic variants associated with MTX efficacy. A total of 30 publications that included 34 genes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 44 publications
2
49
0
Order By: Relevance
“…In our previously published studies, a total of 4 SNPs were identified in 2 genes that encode membrane‐spanning proteins involved in MTX metabolism. These gene polymorphisms were amplified by polymerase chain reaction (PCR), for which the forward and reverse primers were designed by Primer 5 software, as shown in Table .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previously published studies, a total of 4 SNPs were identified in 2 genes that encode membrane‐spanning proteins involved in MTX metabolism. These gene polymorphisms were amplified by polymerase chain reaction (PCR), for which the forward and reverse primers were designed by Primer 5 software, as shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we searched all of the available studies that have explored relationships between single‐nucleotide polymorphisms (SNPs) or variable number of tandem repeat polymorphisms and MTX outcomes in RA patients. Thirty studies were included in our meta‐analysis, and we found that polymorphisms in 2 membrane‐spanning protein‐encoding genes, reduced folate carrier‐1 (RFC‐1)/SLC19A1 (G>A [rs7499], A>G [rs2838956], and 180G>A [rs1051266]) and ABCB1 (rs1045642), are associated with responsiveness to MTX in RA patients . RFC is the first recognized folate transporter whose function as a bidirectional anion exchanger creates an uphill influx of folates, coupled with the downhill efflux of organic phosphates, such as thiamine monophosphate and pyrophosphate .…”
mentioning
confidence: 99%
“…Except for association of recessive and codominant models of rs1801131 in a South Asian population, there has been no evidence for either of these 2 SNPs being related to the efficacy of MTX in RA according to various meta‐analyses . A recent meta‐analysis has showed associations between the MTX response in RA patients for MTHFR A1298C, but not for MTHFR C677T (rs1801133) .…”
Section: Current Knowledge About Pharmacogenetics Of Adsmentioning
confidence: 99%
“…ATIC C347G (rs2372536) is another well‐studied variant related to MTX therapy in RA. Despite the lack of association between rs2372536 polymorphism and the MTX treatment response in some studies, other studies, including meta‐analyses, support the association between rs2372536 polymorphism and MTX response status in some populations . Moreover, another SNP in this gene (ATIC T675C [rs4673993]) may possibly predict responsiveness to MTX in RA patients …”
Section: Current Knowledge About Pharmacogenetics Of Adsmentioning
confidence: 99%
See 1 more Smart Citation